Akibat Hukum Terhadap Pendaftaran Merek Produk Barang Yang Memiliki Persamaan Pada Pokoknya - Siolimbona, Sandra; Haliwela, Nancy Silvana; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Trademarks or names are marks used by companies or businesses on the products they trade because Trademarks are used as identifiers. As stipulated in Law No. 20 Year 2016 on Trademarks and Geographical Indications in Article 1 paragraph (1). Trademarks also cannot be registered when they have elements of similarity in the trademark as stipulated in Article 20-21 of the Trademark and Geographical Indications Law. However, this is contrary to the incident in the chocolate product brands Chacha Delfi and Chacha Lokal, where Chacha Delfi tried to apply for registration at the Directorate General of IPR and KEMENKUMHAM but was rejected because the Chacha Delfi brand has an element of similarity in its principal to the Cha-Cha Lokal product brand, because we know that the Cha-Cha Lokal brand from PT. Mayora who registered the brand first.Purposes of the Research: To know and explain about the procedure of product registration Trademark Chacha Delfi and Cha-Cha Local, which has similarities in essence and know and, analyze the legal consequences of registration of trademarks that have similarities in essen.Methods of the Research: The legal research method used for this research is based on primary, secondary, and tertiary legal materials, and uses a statute approach and conceptual approach and case approach.Results of the Research: The results showed that the Chacha Delfi trademark registration procedure was rejected by the Directorate General of IPR and KEMENKUMHAM, because the trademark did not meet the registration procedures where the trademark has similarities to the pre-existing trademark, namely the local Cha-Cha trademark that has done the trademark registration first. because based on the Trademark Law and PERMENKUMHAM who register first then the trademark will be recognized ownership of the trademark. So that the legal consequences obtained by Chacha Delfi brand is rejected and dismissed to trade products Chacha Delfi brand and subject to sanctions under the Trademark Act and PERMENKUMHAM. Therefore, it is expected that the Directorate General of IPR and KEMENKUMHAM, in order to publish the trademarks that have been registered, so that businesses and other companies can see, so that there is no more Trademark Equation and does not lead to a Trademark Equation dispute.